Visual Astronomy in the Suburbs A Guide to Spectacular Viewing - Cooke, Antony. (Patrick MooreỚ"s Practical Astronomy Series, 2003)
Most amateur astronomers, because they live in or near cities, have to carry out their observing from relatively light-polluted sites. It is possible to reduce the effects of a poor location by the use of CCD imaging, but many observers prefer to look at astronomical objects rather than photograph them. Skill, observing techniques, and modern technology - such as image intensifiers - can now be used to astonishing effect to observe the night sky in real-time. Illustrating the book with images and some of his own superb drawings, Antony Cooke explains how to observe some of the most spectacular objects from less than perfect observing sites.